2021
DOI: 10.1097/cm9.0000000000001401
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and clinical application value of an automatic diagnosis platform for rectal cancer T-staging based on a deep neural network

Abstract: Background: Colorectal cancer is harmful to the patient's life. The treatment of patients is determined by accurate preoperative staging. Magnetic resonance imaging (MRI) played an important role in the preoperative examination of patients with rectal cancer, and artificial intelligence (AI) in the learning of images made significant achievements in recent years. Introducing AI into MRI recognition, a stable platform for image recognition and judgment can be established in a short period. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Using 290 MRI images from 133 patients, a CNN algorithm was developed to automatically segment and classify tumors as either T2 or T3 with an accuracy of 94%. More recently, Wu et al utilized faster regionbased CNNs to create an automatic diagnosis platform for T staging of rectal cancer via MRI (83). The study found AUC of 1 for T1-T4 stages in the horizontal plane and 0.96, 0.97, 0.97, and 0.97 for T1-T4, respectively.…”
Section: Therapeutics: Predicting Response To Therapy Personalizing A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Using 290 MRI images from 133 patients, a CNN algorithm was developed to automatically segment and classify tumors as either T2 or T3 with an accuracy of 94%. More recently, Wu et al utilized faster regionbased CNNs to create an automatic diagnosis platform for T staging of rectal cancer via MRI (83). The study found AUC of 1 for T1-T4 stages in the horizontal plane and 0.96, 0.97, 0.97, and 0.97 for T1-T4, respectively.…”
Section: Therapeutics: Predicting Response To Therapy Personalizing A...mentioning
confidence: 99%
“…More recently, Wu et al. utilized faster region-based CNNs to create an automatic diagnosis platform for T staging of rectal cancer via MRI ( 83 ). The study found AUC of 1 for T1-T4 stages in the horizontal plane and 0.96, 0.97, 0.97, and 0.97 for T1-T4, respectively.…”
Section: Therapeutics: Predicting Response To Therapymentioning
confidence: 99%
“…Deep learning has also been applied in the T stage to realize more precise automatic T staging. Wu et al 16 used Faster R‐CNN to construct an automatic diagnosis platform based on MRI, with AUCs of 0.95–1.0 for the T1, T2, T3, and T4 stages in the horizontal, sagittal, and coronal planes.…”
Section: Clinical Applications Of Ai In Rc Based On Mrimentioning
confidence: 99%
“…In 3D-T2 weighted MRI, the 3D full collaborative network architecture based on DL could segment CRC more reasonably and effectively than other techniques[ 35 ]. In the high-resolution MRI image of rectal cancer, the use of a faster region-based convolution NN (Faster R-CNN) had a high accuracy in evaluating tumor boundaries[ 36 , 37 ]. Circumferential resection margin is one of the key factors affecting the treatment decision of CRC patients.…”
Section: Use Of Ai In Diagnosis Of Crcmentioning
confidence: 99%